Mass transfer analysis and kinetic modeling for process design of countercurrent membrane supported reactive extraction of carboxylic acids. (February 2022) - Gössi, Angelo; Riedl, Wolfgang; Schuur, Boelo
Graphical abstract: Highlights: Mass transfer rates for a new type of highly robust membrane contactor measured. The mass transfer resistance was identified to be in the membrane phase. Countercurrent multi-stage extraction model for different carboxylic acids developed. Excellent agreement between model and experimental validation. Abstract: Countercurrent membrane supported reactive extraction (MSRE) was studied for removal of carboxylic acids from aqueous streams with a PTFE capillary membrane. Analysis of the mass transfer rates was performed to support modeling of the process. Total mass transfer coefficients ranging from 2.0·10 -7 to 4.0·10 -7 m/s were obtained when extracting lactic acid with 20 wt% tri-N-octyl amine in 1-decanol with membrane thicknesses of 260 µm and 80 µm. The limiting mass transfer resistance in all experiments was in the membrane phase. The developed model based on mass transfer and reaction in parallel allows to predict countercurrent extraction. Experimental validation with 5, 7 and 12 m long membrane modules showed excellent accordance for two acids, validating the model simulations. Simulated membrane contactor lengths required for single, two and three countercurrent stages varied between 10 and 39 m/stage for lactic, mandelic, succinic, itaconic and citric acid, depending on acid, membrane, and diluent.